Cistus incanus from Strandja Mountain as a Source of Bioactive Antioxidants - Dimcheva, Vanya (Plants (Basel), 2018)
The purpose of the present study is to survey the extraction conditions and explore the antioxidant potential of the wild herb Cistus incanus, which is non-traditional in Bulgarian ethnomedicine and widespread in the Strandja Mountain. The influence of the extraction time (0–500 min) and solvent composition (0–50% ethanol in water) on the polyphenols, flavonoid yields and on the antioxidant capacity of the extracts of leaves, stalks (wood parts) and bud mixture were studied. The antioxidant capacity (AOC) was evaluated by use of scavenging assays of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. Total polyphenol and flavonoid contents were quantified using UV–vis (ultraviolet-visible) spectrophotometry. The optimal yield of the desired components was obtained with 30% ethanol in water solvent at the 390th min of extraction time. In addition, the influence of seasonality (winter and summer Cistus incanus), and of the different aerial parts—hard-coated seeds, buds, and a mixture of leaves and stalks of the wild plant—on the presence of polyphenols, flavonoids, and AOC were investigated. The present work revealed that the high values of polyphenols, flavonoids and the high AOC occurred not only in the summer leaves, but were also found in the winter leaves, hard-coated seeds, buds, and stalks. Based on the obtained results, the Cistus incanus from Strandja Mountain could be an excellent new source of natural antioxidants in food and for the pharmaceutical industries.